The Current Understanding of the Endocrine Effects From Immune Checkpoint Inhibitors and Recommendations for Management. Issue 3 (19th July 2018) - Girotra, Monica; Hansen, Aaron; Farooki, Azeez; Byun, David J; Min, Le; Creelan, Ben C; Callahan, Margaret K; Atkins, Michael B; Sharon, Elad; Antonia, Scott J; West, Pamela; Gravell, Amy E; et al.
Abstract: Clinical trials in the past decade have established the antitumor effects of immune checkpoint inhibition as a revolutionary treatment for cancer. Namely, blocking antibodies to cytotoxic T-lymphocyte antigen 4 and programmed death 1 or its ligand have reached routine clinical use. Manipulation of the immune system is not without side effects, and autoimmune toxicities often known as immune-related adverse events (IRAEs) are observed. Endocrine IRAEs, such as hypophysitis, thyroid dysfunction, and insulin-dependent diabetes mellitus, can present with unique profiles that are not seen with the use of traditional chemotherapeutics. In this Review, we discuss the current hypotheses regarding the mechanism of these endocrinopathies and their clinical presentations. Further, we suggest guidelines and algorithms for patient management and future clinical trials to optimize the detection and treatment of immune checkpoint–related endocrinopathies.